Kaempferol-rich Thespesia lampas leaf extract mitigates gentamicin-induced nephrotoxicity via antioxidant and anti-inflammatory mechanisms in wistar rats - Shweta Shamrao Dhavane; Ravindra Bhimraj Laware (Journal of Applied Pharmaceutical Research, 2026)
Background: Gentamicin-induced nephrotoxicity (GIN) is a major limitation of aminoglycoside therapy and a common cause of acute kidney injury (AKI). The underlying mechanisms involve excessive oxidative stress and activation of inflammatory signaling pathways, particularly the nuclear factor-κB (NF-κB) pathway. Natural flavonoids such as kaempferol possess strong antioxidant and anti-inflammatory properties. Thespesia lampas, traditionally used in renal disorders, is rich in kaempferol, necessitating scientific validation of its nephroprotective potential. Methodology: ALE was characterized using HR-LCMS, confirming kaempferol as the major flavonoid (20.5 ± 2.8 mg/g extract; 2.05 ± 0.28% w/w). Antioxidant activity was assessed by the DPPH assay, demonstrating potent free radical scavenging (IC₅₀ = 62.4 µg/mL) comparable to rutin standard (IC₅₀ = 48.6 µg/mL). Rats received ALE orally at doses of 100, 200, and 400 mg/kg for 28 days, while nephrotoxicity was induced by gentamicin (50 mg/kg/day, i.p.) during the final 10 days. Renal function markers, oxidative stress parameters, pro-inflammatory cytokines (TNF-α, IL-6), NF-κB (p65/p50) nuclear translocation, and renal histopathology were evaluated. Results and Discussion: Gentamicin caused significant renal dysfunction, oxidative imbalance, elevated inflammatory cytokines, and increased NF-κB activation. ALE treatment produced dose-dependent nephroprotection, with the 400 mg/kg dose markedly restoring renal biomarkers, improving antioxidant defenses, suppressing inflammatory mediators, and ameliorating histopathological damage. Conclusion: Kaempferol-rich Thespesia lampas ALE confers significant protection against gentamicin-induced nephrotoxicity by attenuating oxidative stress and inhibiting NF-κB–mediated inflammation, highlighting its potential as a therapeutic agent for drug-induced renal injury.